Evaluation of physicochemical and biological properties of chitosan/poly (vinyl alcohol) polymer blend membranes and their correlation for Vero cell growth. (10th February 2016) - Sharma, Parul; Mathur, Garima; Dhakate, Sanjay R.; Chand, Subhash; Goswami, Navendu; Sharma, Sanjeev K.; Mathur, Ashwani
Graphical abstract: Highlights: CS membrane physicochemical properties changes drastically on blending with PVA. Pseudo-second order BSA and ammonia sorption kinetics was observed on membranes. Specific growth rate of Vero cells higher on blend membranes than CS membrane. Linear correlation between water holding and doubling time of Vero cells on CS/PVA. CS/PVA membranes can be an alternative carrier material for Vero cell proliferation. Abstract: The blend membranes with varying weight ratios of chitosan/poly (vinyl alcohol) (CS/PVA) (1:0, 1:1, 1:2.5, 1.5:1, 1.5: 2.5) were prepared using solvent casting method and were evaluated for their potential application in single-use membrane bioreactors (MBRs). The physicochemical properties of the prepared membranes were investigated for chemical interactions (FTIR), surface morphology (SEM), water uptake, protein sorption ( q e ), ammonia sorption and growth kinetics of Vero cells. CS/PVA blend membrane having weight ratio of 1.5:1 had shown enhanced membrane flexibility, reduced water uptake, less protein sorption and no ammonium sorption compared to CS membrane. This blend membrane also showed comparatively enhanced higher specific growth rate (0.82/day) of Vero cells. Improved physicochemical properties and growth kinetics obtrude CS/PVA (1.5:1) as a potential surface for adhesion and proliferation with possible application in single use membrane bioreactors. Additionally, new insight explaining correlation between water holding (%) of CS/PVA (1.5:1) blend membrane and doubling time ( t d ) of Vero cells is proposed.